The Road Not Taken: Rabbi Shlomoh Zvi Schück and the Legacy of Hungarian Orthodoxy - Ferziger, Adam S. (Hebrew Union College annual, 2008)
The triumph of the Orthodox separatist forces at the Hungarian Jewish Congress of 1868-69 facilitated the swift integration of the ultra-Orthodox viewpoint into the mainstream and the simultaneous decline of the moderate Orthodox camp in numbers and influence. Nevertheless, the latter's members did not completely disappear. Some declared themselves "Status Quo," remaining committed to the pre-Congress reality and refusing to associate with either the newly founded official Orthodox framework or the Neolog-dominated Hungarian Jewish Congress. Yet there were also individuals who maintained affiliation with Orthodoxy, but continued to express opinions that went against the dominant tide. One such figure was Rabbi Shlomoh (Salamon) Zvi Schück (1844-1916). This article draws attention to the unique contours of R. Schück's approach to the divisions among Hungarian Jewry and its evolution during his lifetime. In the process it demonstrates how his outlook was actually shaped by the more adversarial voices that held sway. Moreover, it suggests what may be discerned regarding the main direction of Hungarian Orthodoxy by highlighting this road not taken. It considers as well the implications of this model for analyzing broader themes in the history of Jewish Orthodoxy.